Buddhist heritage of Orissa : [from Kalinga to Sri Lanka] - Mohanty, Bimalendu; Mohanty, Bimalendu (Vohra Publishers & Distributors, 2009)
section A. Buddhism and Orissa -- section B. Buddhist art and architecture -- section C. Buddhism and its impact